Terapi SEFT dalam Upaya Menurunkan Tekanan Darah pada Penderita Hipertensi di Wilayah Puskesmas Kersanegara –Tasikmalaya - Cahyati, Peni; Kustiawan, Ridwan; Mariani, Dini; Rosdiana, Ida; Somantri, Iwan (Universitas Baiturrahim, 2024)
Non-Communicable Diseases (NCDs) are diseases that are currently the highest cause of death in Indonesia. PTM sufferers at the Kersanegara Community Health Center, especially hypertension and diabetes mellitus, are increasing over time. In Tasikmalaya City, based on data from the Health Service, in 2023, there were 55,999 people with hypertension. Therefore, one of the efforts of the Kersanegara Community Health Center to improve the quality of life for PTM sufferers so that it is more optimal is by holding Prolanis activities. Hypertension is one of the risk factors that most influences the incidence. heart and blood vessel disease. Hypertension often shows no symptoms, so it is only realized when it has caused organ disorders such as heart dysfunction or stroke. The regional development team for the Tasikmalaya health polytechnic applied undergraduate and nursing study program collaborates with the Kersanegara Community Health Center to provide health services with a proactive approach that is implemented in an integrated manner involving participants through a chronic disease management program. The activities carried out were providing exposure to material about hypertension and introducing SEFT therapy to 53 people suffering from hypertension with the aim of helping lower blood pressure. The results of the evaluation of this community service activity achieved the goals that had been set, namely 100% participant attendance, all participants were active, there was an increase in knowledge, participants were able to mention the symptoms and signs of hypertension, the consequences of hypertension, the treatment and care of hypertension and 2 participants understood and explained about therapy. SEFT with the language style of each community service participant. In general, hypertension management consists of pharmacological therapy (using anti-hypertension drugs) and non-pharmacological therapy, namely by interpreting stress with relaxation techniques, one of which is SEFT therapy.